Peak Expiratory Flow Rate in Pregnant Women - Sunyal, Dipok Kumar; Amin, Md Ruhul; Ahmed, Abeda; Begum, Shameema; Begum, M; Rahman, N (Journal of Bangladesh Society of Physiologist, 2008)
In the present study peak expiratory flow rate (PEFR) were estimated in pregnant women during different trimester to observe the alteration in air flow rate during pregnancy. This study was carried out in the department of Physiology of Dhaka Medical College from July 2004 to June 2005. For this purpose, total 100 women with age ranged from 25 years to 35 years without any recent history of respiratory diseases were selected and divided into 25 healthy non-pregnant women as control and 75 normal pregnant women as study group. Study group was further divided into 25 in first trimesters, 25 in second trimester and 25 in third trimesters of pregnancy. All the subjects belonged to lower socioeconomic class. The PEFR was estimated by using an automatic spirometer. The measured values and percentage of predicted values of PEFR were estimated during the 1st, 2nd, 3rd trimesters of pregnant women and non-pregnant women. Statistical analysis of data were done by un paired student's ‘t'test. The PEFR was significantly lower in both 2nd and 3rd trimester pregnant women than that of non-regnant women. Again the PEFR was significantly lower in 3rd trimester than that of 1st trimester of pregnant women. There were no statistically significant difference of PEFR between the non-pregnant and 1st trimester; between the 1st trimester and 2nd trimeste; and between the 2nd trimester and 3rd trimester of pregnant women. It may be concluded that PEFR were progressively decreased throughout the pregnancy, most likely due to mechanical effects of progressively increased size of uterus that progressively decreases lung volumes and capacities. Key Words: Expiratory Flow Rate, Pregnancy, Uterus DOI:10.3329/jbsp.v2i0.979 J Bangladesh Soc Physiol. 2007 Dec;(2): 20-23.